Urtica dioica for benign prostatic hyperplasia - Posadzki, Pawel; Kongkaew, Chuenjid; Ernst, Edzard (Journal of herbal medicine, 2025)
As of 2019, globally, there were 94 million prevalent cases of benign prostatic hyperplasia. This systematic review evaluates the effectiveness of Urtica dioica as a treatment of benign prostatic hyperplasia (BPH). MEDLINE, Embase, CINAHL, the Cochrane Central Register of Controlled Trials (CENTRAL), Web of Science and ClinicalTrials.gov were searched from databases inceptions to February 2024. Randomized clinical trials (RCTs) investigating Urtica dioica (with or without usual care) for treating BPH in human subjects were considered. The GRADE approach was used to evaluate the certainty of evidence. Six RCTs with a total of 1210 patients met the inclusion criteria. Risk of bias of the included studies was mostly unclear or high. Meta-analyses showed that, compared with controls (placebo, usual care), Urtica dioica improved slightly BPH symptoms measured with the International Prostate Symptom Score (IPSS) at follow-ups of up to 12 months (standardized mean difference [SMD] -2.06, 95% confidence intervals [CI] [-3.22, -0.91] very low certainty evidence), reduced prostate specific antigen (PSA) levels (mean difference [MD] -0.37 ng/ml, 95% CI [-0.50, -0.23] low certainty evidence) but the interventions had little effect on quality of life (SMD -0.59, 95% CI [-1.57, 0.38] very low certainty evidence). The main reasons for downgrading the evidence were study limitations, inconsistency, and imprecision. All six studies reported adverse-effects; stating that none had occurred. There is some promising evidence to support the effectiveness of Urtica in reducing the symptoms of BPH. Future, larger and more rigorous studies might reduce the existing uncertainties. •The evidence for the effectiveness of the herb is, promising, and warrants further investigations.•We found some clinically meaningful improvements of Urtica for benign prostatic enlargement.•However, we still need more and better-quality studies to draw any definite conclusions.